Development of Learning Biology Based on Socio Scientific Issue Oriented Strengthening Pancasila Student Profiles - Uji, Andi Tenri; Bahri*, Arsad; Jamaluddin, Asham Bin; HS, Syamsul Bahri (Universitas Syiah Kuala, 2025)
Pancasila profile students (PPS) at SMA Negeri 21 Makassar are still classified as low, therefore that done development new namely the STARS model which aims develop a biology learning model based on SSI which focuses on strengthening PPS. This research employed a research and development approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Subject study are Teachers and participants educate class X of SMA Negeri 21 Makassar. The STARS model of SSI learning is designed for increase skills think critical, creativity, and independence participant educate, which is the core of PPS. The results of study show that the STARS model is very valid with average score 4.5. Practicality test shows the STARS model easily applied with average score of 4.6, and get response positive from teachers and participants educate. The effectiveness test showed a significant improvement in students critical thinking (N-Gain = 0.45), creativity (N-Gain = 0.50), and independence (N-Gain = 0.40). This STARS mode no only support achievement competence academic, but also strengthening values character in accordance demands independent curriculum. Findings this give contribution in create design innovative and relevant learning for support education 21st century